The Effect of Chalcone Isomerase Gene Silencing on Pigment Production Pathway in Petunia hybrida with RNAi Technology - F. Keykha Akhar; A.R. Bagheri; N. Moshtaghi; M. Fakhrfeshani (Majallah-i ̒Ulum-i Bāghbānī, 2023)
Introduction Flower color is one of the most significant characteristics in ornamental plant breeding. New varieties of various plants in relation to their flower color have been obtained by monitoring the expression levels of genes involved or regulating the flavonoid and anthocyanin biosynthesis pathway. Flavonoids possess significant and diverse biological functions. They are the major pigments for flowers, fruits, seeds, and leaves. They are natural products that contain a C6-C3-C6 carbon framework and are synthesized by a branched pathway that yields both colored and colorless compounds. The gene encoding chalcone isomerase (CHI) is among the genes and enzymes identified in the flavonoid pathway. This enzyme catalyzes the isomerization of naringenin chalcone into the corresponding flavanone. CHI enzyme belongs to the family of isomerases, specifically the class of intramolecular lyases. Chalcone isomerase has a core 2-layer alpha/beta structure and has attracted much attention recently due to its role in stress response and pigment production. One of the most effective methods of genetic engineering is the reduction of flower pigments by suppression of required enzymes for their biosynthesis. RNA interference (RNAi) has provided the tool for the investigation of genes involved in the production of flower color. Silencing of any gene in the anthocyanin biosynthetic pathway can result in reduced or inhibited anthocyanin production. RNAi technology is an effective gene silencing method and a powerful tool for studying gene function and development of new traits by transformation of viral RNA or hairpin RNA (hpRNA) constructs into plants. The processing of dsRNA into 21-23-nt small interfering RNAs (siRNAs), and the mediators of RNAi, triggers cognate mRNA degradation. The hpRNAi methodology simply requires a transgene construct containing an inversely-repeated sequence of the target gene flanked with a promoter and terminator which effectively function in plants.